(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Fine arts of Uzbekistan have a unique history. Leafing through the pages of this history, we become witnesses of the fact that along with poetry, music, folklore, applied art, the art of manuscripts also flourished.